The reimbursement action brought by an insurer is governed by the law of the place where the damage occurred (commentary on the ECJ judgement of May 12.2023) - OrtegaGiménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The Court of Justice of the European Union has recently handed down a judgment, dated 17 May 2023, in which it ruled on the law applicable to actions for reimbursement of damages in an international context. The judgment concludes that an action for reimbursement brought by an insurer, which has paid a certain amount to an accident victim, against the tortfeasor (or his insurer) is governed by the law of the place where the damage occurred. It is the law of the place where the damage occurred that also determines the limitation period.